Population comparison of innate and plastic host plant preference and performance in a polyphagous insect - Karlsson Green, Kristina; De Pasqual, Chiara; Litto, Maria; Anderson, Peter (Frontiers in Ecology and Evolution, 2024)
During decision-making, animals may use either innate or plastic behaviours. This has been suggested to be important for generalist phytophagous insects where females need to assess a large range of cues during host plant selection for oviposition. To facilitate the choice, generalists may thus use innate preference hierarchies among host plants combined with phenotypic plasticity based on earlier host experience, but if populations differ in whether they rely on innate or plastic factors during decision-making is not well-known. Females from an Egyptian population of the polyphagous moth Spodoptera littoralis has previously been found to shift preference between plants in their innate preference hierarchy depending on larval host plant experience. We studied the innate preference hierarchy for three host plants (cotton, cabbage and cowpea), and whether the hierarchy shifts based on larval host plant experience, in a Northern range margin population (Italy) and a core population (Kenya) of S. littoralis, to see if and how these traits vary across populations. In addition, we studied larval performance on the three host plants in all three populations. The Italian and Kenyan populations had different innate preference hierarchies, and both hierarchies differed from the hierarchy that has previously been found in the Egyptian population. Furthermore, the host plant selection of ovipositing females was affected by larval diet in the Italian and Kenyan population, but the larval host plant experience did not completely shift the preference hierarchy as in the Egyptian population. This indicates that not only host plant preference per se, but also phenotypic plasticity during host plant selection can vary between populations. We further found that the populations responded differently to larval diet for some performance traits. However, it was only the Italian population that showed indications of any link between preference and performance, as they had slower development on their least preferred host plant. Overall, preference divergence between populations seems not to be driven by local variation in larval performance.